Pelatihan dan Pendampingan Pengelolaan Keuangan Usaha dan Pemanfaatan Aplikasi Akuntansi UKM - Febrianty Febrianty; Mutiara Lusiana Annisa; Yobi Nagoya Pratiwi; Triyana Putri; Putri Utami; Eka Lestari (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: SMEs are one of the vehicles that drive the country's economy in Indonesia. The existence of SMEs plays a major role in increasing the progress of a business wheel in Indonesia. As the driving force of the economy, SMEs must manage their finances well. Good financial management can be seen from how SMEs can plan business activities and control business activities properly. The purpose of this community service activity is to increase the application of science and technology in the Asyik Suka SME Community for the application of methods for managing business finances and the use of financial applications. Method: One of the methods used to manage finances well is to use Kakeibo. Kakeibo is a way of managing finances introduced by the Japanese. The media used in Kakeibo are envelopes and notes related to financial planning. Service activities will be carried out with the UKM Asyik Suka Community in Palembang City. In addition to using Kakeibo, service activities are also supported by the use of the SME Accounting Application. The SME Accounting Application is used to facilitate business activities by entering information related to SME finance. The method of service activities is carried out using lecture media and the practice of using Kakeibo and UKM Accounting Applications. Results: Based on the results of the questionnaire graph that the participants are in the 70-80% interval, it means that this service activity has a positive impact on increasing the application of science and technology to the participants. Conclusion: The service activities that have been carried out at the home of the Chairperson of the Asyik Suka MSME Community, namely Mrs. Yeni Rozak and the participants of the Asyik Suka MSME activity, totaling 11 MSME owners, from the discussion of material and direct practice to the participants of the Asyik Suka MSME Community service were greatly helped and increased knowledge about the use of technology to help businesses, especially in the use of MSME Accounting Application technology.